2004
DOI: 10.1111/j.1745-7599.2004.tb00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Caring Behaviors As Perceived by Nurse Practitioners

Abstract: NPs often work in clinic situations where productivity is the most valued characteristic and where little time is afforded for identifying caring behaviors of the NP and/or establishing a caring relationship with the patient. NPs must be extremely conscious of the need not to "throw out the baby with the bathwater" and sacrifice characteristics that are inherent in nursing for those emphasized in primary care practice. As their responsibilities in the health care setting continue to expand, NPs must continuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
30
2
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 32 publications
7
30
2
4
Order By: Relevance
“…Descriptive statistics (mean, standard deviation, range, frequency, and percent) were obtained on the demographics for each group. For statistical analyses, CBI mean scores of the NP sample ( N = 36) by demographics and by caring groups were calculated (Green, 2004). As explained previously, one NP and 30 DWPSQs had to be deleted from a nursing home setting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Descriptive statistics (mean, standard deviation, range, frequency, and percent) were obtained on the demographics for each group. For statistical analyses, CBI mean scores of the NP sample ( N = 36) by demographics and by caring groups were calculated (Green, 2004). As explained previously, one NP and 30 DWPSQs had to be deleted from a nursing home setting.…”
Section: Methodsmentioning
confidence: 99%
“…Seventeen rural clinics and 19 urban clinics were represented in the study. Both areas of practice, rural and urban, were well represented by both male and female NPs (Green, 2004). No literature was found that explored perception of caring behaviors by male and female NPs in rural and urban settings.…”
mentioning
confidence: 99%
“…Provided that nursing is mostly relational in nature, it is likely that more self-encouraged nurses remain focused on patients' needs, encourage patients to call with problems, continue to look for different ways to deal with their concerns and problems, and persevere in keeping open and positive the mutual emotional flow, i.e. adopt more expressive caring behaviours (Green, 2004;Wolf et al, 1994).…”
Section: Use Of Emotions (Self-encouragement)mentioning
confidence: 99%
“…Although a wide range of caring behaviours can be found in the literature (e.g. von Essen & Sjödén, 2003;Green, 2004;Greenhalgh et al, 1998;Khademian & Vizeshfar, 2008;Lee-Hsieh, Kuo, Tseng, & Turton, 2005;Wolf, Giardino, Osborne, & Ambrose, 1994), they can be classified according to the six dimensions of nursing presence (Doona, Chase, & Haggerty, 1999;Godkin, 2001;Godkin & Godkin, 2004). As we will show below, their content helped us to develop the instrument for measuring the caring behaviours in this research.…”
Section: Introductionmentioning
confidence: 99%
“…There are ongoing discussions among investigators on various aspects of care in nursing (4). In a number of literature reviews (2,5) and analyses of care (6,7), the meaning of care from the perspective of nurses was explored for nursing practitioners (8)(9)(10)(11), there is however, little research exclusively concerned with registered nurses (RNs) at the emergency department.…”
Section: Introductionmentioning
confidence: 99%